CATCH-UP MODERNIZATION RUSSIAN NATIONAL ECONOMY IN INNOVATION MODELS - M. Ashurova (Вестник университета)
In the article the essence and character of undulating catch-up modernization of the Russian economy. It is noted that in the context of macroeconomic theory, to modernize the national economy affects the direction of the previous periods of its transformation, the intensity and depth of institutional changes.